Mengelola Perbedaan, Membangun Kembali Nilai Persaudaraan: Kajian Studi Perdamaian terhadap Memori Kolektif dalam Film Cahaya dari Timur Beta Maluku - Mofun, Costantinus Ponsius Yogie (IAKN Ambon, 2023)
This concept of diversity is one of the parts that can be found in social life. This concept is also often found in various regions of Indonesia and one of them is in Maluku. With the existence of various diversity in Maluku, it is not used as a difference but it becomes a very strong kinship system. The system that was built was based on genealogical relationships as well as based on traditional and cultural values which later became a philosophy for the Moluccans. The life of the basudara people became very close. But when conflicts occur, the relationship begins to erode and form various differences based on religious identity. Thus the purpose of this paper will discuss the collective memory built on the customs and cultural values of the basudara people using the analysis of the film